Synthesis of Aluminum Oxide Nanoparticle Adsorbents from Waste Aluminum Foil and Assesses Their Efficiency in Removing Lead (II) Ions from Water - Aktaruzzaman, Md; Salam, Sayed M.A.; Mostafa, M.G. (Tropical Aquatic and Soil Pollution, 2024)
Aluminum oxide nanoparticles have recently been applied to water treatment as adsorbents by researchers. In this study, aluminum oxide nanoparticles (AlONPs) were synthesized using scrap aluminum foil through a straightforward, inexpensive, and green approach, and their performance in adsorbing lead (II) ions from an aqueous solution was assessed. The synthesized nanoparticles were characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), and Scanning Electron Microscopy with Energy-Dispersive X-ray Spectroscopy (SEM-EDX) to analyze their bonding nature, particle size, phase composition, and surface morphology. They exhibited an average particle size of 32.73 nm, consisting predominantly of γ-Al2O3, with small amounts of α-Al2O3 and a minor unknown phase. The lead adsorption efficiency was evaluated under optimized parameters, including pH, contact time, and doses of both adsorbate and adsorbent. The results demonstrated that the AlONPs achieved a 98% removal efficiency within 30 minutes of contact time at a pH of 5.5. Additionally, the Freundlich adsorption isotherm model (R² value of 0.9972) and the pseudo-second-order kinetic model (qe) value of 37.97 mg/g) were shown to fit the lead adsorption process better than other models. Hence, the synthesized AlONPs offer potential as nanoparticle adsorbents for removing lead (II) ions from aqueous solutions.